Slang as a Communication Strategy Employed by Jay and Jake of ENHYPEN in the Daebak Show Podcast - Qodriyati, Nurul Lailatul; Firdaus, Moh Iqbal; Anggraini, Diah Retno (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the use of English slang by Jay and Jake from Enhypen during their guest appearance on Eric Nam’s Daebak Show Podcast. Employing a descriptive qualitative approach, it investigates the morphological forms, semantic shifts, and pragmatic-social functions of slang terms used in the podcast. The primary data comes from the episode titled “ENHYPEN’s JAY & JAKE had ‘FATE’ to join Eric Nam | DAEBAK SHOW S3 EP12,” released on August 8th, with a duration of 52 minutes. The analysis focuses on spontaneous, informal English expressions from the idols, revealing how slang terms such as "gotta," "kinda," and "vibe" signal group membership and a sense of belonging among youth and fans. This research demonstrates that slang functions not only as a tool for informal communication but also as a form of emotional expression and a means of establishing social identity and relatability within a global audience. The study emphasizes how slang reflects contemporary youth culture and the impact of media platforms in shaping language use. A total of 12 distinct slang terms were identified, several of which served multiple linguistic functions across three analytical categories, resulting in 14 instances of categorized usage. While the sample is limited to two speakers in a single episode, the focused analysis offers valuable insights into language use among K-Pop idols. This research contributes not only to understanding the role of informal linguistic practices in cross-cultural communication but also offers practical insights for English language teaching (ELT), such as integrating contextualized slang into classroom instruction, as well as for media discourse analysis and studies of global youth identity in digital environments.